THE HEALTH OF TALENT MANAGEMENT PRACTICE’S FACTOR ANALYSIS OF PT XYZ, WEST JAVA - Supriyadi, Alya Sania; Syarifuddin, Syarifuddin (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
This paper aims to analyze the health of talent management practice of PT XYZ. As a telecommunication company with good credibility, PT XYZ should keep trying to improve the employee's engagement by manage their talent management according to the data the employee engagement has decreasing every year in the amount of 1-3%, the result of a lack of employee engagement can make 18% more in high turnover. Accordingly, this paper outlines four main factors that may affect the health of talent management (deployment-diagnosis-development-demarcation). The method used in this research is a descriptive method with probability sampling methods with simple random sampling techniques. Data is processed through the first order and second-order confirmatory factor analysis, using software AMOS version 24 (n:130). Results of this study showed that Based on the descriptive analysis it is known that Deployment has an average value of 84.3% which include in the very high category, Diagnosis has an average score of 85% which include in the very high category, Development has an average score of 83.042% which include in the high category, while Demarcation has an average value 82.71% which include in the high category.Keywords: Demarcation, Deployment, Development, Diagnosis, Talent Management